Based on the research results, Elementary School Teachers still emphasized on cognitive and psychomotor domain in social education learning. Therefore, the learning achievement of Social Education was still meaningless in studentsâ real life. In Law No. 2 - Senen, Anwar (Universitas Muhammadiyah Purwokerto, 2014)
Based on the research results, Elementary School Teachers still emphasized on cognitiveand psychomotor domain in social education learning. Therefore, the learningachievement of Social Education was still meaningless in studentsâ real life. In Law No.20/2003 explained that the aims of national education were: to make students creative,autonomous, democratic, and responsible. To develop social education material becamemore meaningful, teachers needed to implement constructivistic paradigm.Key words: Social Education learning, constructivistic paradigm